Study of flow and heat transfer in combination of curved and straight tubes in square arrangement at a subcritical Reynolds number of 35000 - Kunal,; Dhiman, Sushil Kumar (Edelweiss Applied Science and Technology, 2025)
Numerical analysis of flow dynamics and heat transfer from the external surface of four cylinders in a square arrangement has been conducted in this study. The combination of curved and straight tubes, which finds application in waste heat recovery recuperators, has been investigated. The curved tubes have been placed in upstream positions in concave and convex configurations. All the tubes are subjected to a constant heat flux condition. The study has been carried out at a subcritical Reynolds number of 35,000. The spacing ratio between the cylinders has been varied from 1.5 to 4.0, and the curvature ratio has been varied from 0.5 to 1.5. Local and overall heat transfer and pressure at different heights and at different angular distances have been investigated. The computations have been conducted in commercial Ansys Fluent software using the k-kl-ω turbulence model. The heat transfer, in general, is found to increase when a combination of curved and straight tubes is used instead of a conventional straight tube combination. Maximum heat transfer enhancement is found in CX-ST CR 1.5 SR 1.5. In terms of heat transfer ratio, CX-ST CR 1.5 SR 3.0 is the most efficient, with a 65.43% increase in heat transfer.